2009
DOI: 10.1002/jbm.a.32552
|View full text |Cite
|
Sign up to set email alerts
|

Friction properties of novel PVP/PVA blend hydrogels as artificial cartilage

Abstract: In this work, novel polyvinylpyrrolidone (PVP)/polyvinylalcohol (PVA) blend hydrogels were prepared by repeated freezing-thawing cycles. The factors that influenced friction properties of blend hydrogels, such as PVP content, contact load, sliding speed, and lubrication condition, were mainly studied by sliding with stainless steel ball. The results showed that friction coefficients of the PVP/PVA blend hydrogels were definitely dependent on such influence factors. The friction system consisting of blend hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 23 publications
2
27
0
Order By: Relevance
“…The characteristics of physical hydrogels formed by freezing/thawing method are comparable with that of articular and meniscal cartilage [18], and, in addition, the excellent wear resistance and tribological properties [7,8,[14][15][16], make them suitable biomaterials for tissue engineering applications.…”
Section: Pva/pvp Hydrogel Structurementioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of physical hydrogels formed by freezing/thawing method are comparable with that of articular and meniscal cartilage [18], and, in addition, the excellent wear resistance and tribological properties [7,8,[14][15][16], make them suitable biomaterials for tissue engineering applications.…”
Section: Pva/pvp Hydrogel Structurementioning
confidence: 99%
“…PVA and PVP have been demonstrated to form a thermodynamically miscible pair [12,13], their chains interacting by hydrogen bonds due to hydroxyl groups of PVA and proton accepting carbonyl group of PVP ring. By adding PVP to PVA hydrogels, it was observed that PVP enhances lubricity, mechanical and tribological characteristics [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a detailed understanding of the surface roughness of articular cartilage is important to understand how natural joints behave. Knowledge of surface roughness will also be important for the development of new synthetic or tissue engineered materials to replace diseased or damaged articular cartilage (Ateshian, 2007;Danisovic et al, 2012;Ma et al, 2010). Articular cartilage in need of replacement is typically damaged Espino, 2011, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Adding polyethylene glycol [182] and acrylamide [181] into PVA during annealing can get both good mechanical properties and lubricity. Introducing poly(vinyl pyrrolidone) into PVA hydrogel can enhance the mechanical properties and decrease friction coefficient due to the formation of hydrogen bond [183][184][185]. Except the incorporation of hydrophilic polymers such as polyacrylamide and poly(vinyl pyrrolidone) into PVA by blending, a hydrophilic-hydrophobic copolymer hydrogel of PVA and poly(ethylene-co-vinyl alcohol)(EVAL) has also been studied.…”
Section: Hydrogels Used As Articular Cartilage Biomaterialsmentioning
confidence: 98%